Analisis Pengendalian Kualitas Pada Produk Songkok Menggunakan Metode FMEA dan FTA Pada CV. ABC - Ahmad Fasih Hasibu Dzikri; Hidayat Hidayat; Yanuar Pandu Negoro (G-Tech: Jurnal Teknologi Terapan, 2024)
As the industrial world continues to advance, competition between companies is becoming increasingly fierce. To enhance customer satisfaction, companies must be able to provide the best quality. CV. ABC is a manufacturing company focused on producing *songkok* (traditional caps). However, during the production process, the company faces several challenges, particularly with defective products. The purpose of this study is to conduct quality control using the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods.The results of the FMEA calculations are as follows: the sewing machine encountered needle breakage issues with an RPN (Risk Priority Number) of 448, dull and poorly maintained cutting tools during the stitching process with an RPN of 576, low-quality raw materials with an RPN of 504, and a substandard screen-printing tool with an RPN of 648. Through the FTA method, the causes of failure include human factors, machine malfunctions, and poor-quality raw materials.